2010
DOI: 10.1227/01.neu.0000365826.15986.40
|View full text |Cite
|
Sign up to set email alerts
|

Results After Lumbar Decompression With and Without Discectomy

Abstract: Patients who underwent single-level lumbar decompression with or without discectomy had similar outcomes as those who underwent the conventional approach. Although of modest clinical significance, the transspinous approach may afford early mobilization and reduced postoperative pain while providing a satisfactory neurological and functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 47 publications
2
17
0
1
Order By: Relevance
“…The first therapeutic approach should always be the conservative treatment and our study included only patients that had undergone conservative treatment, but failed to show adequate response. This is however consistent with other recent randomized controlled studies have shown greater improvements in patients after surgery than after conservative treatment [12] [14]. A recent systematic review comparing surgery to conservative treatment in LSS suggested that for patients with radicular pain caused by LSS, in whom a trial of 3 -6 months of conservative treatment had failed, surgery did not improve walking ability but improved pain, function than continuing conservative treatment [10].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The first therapeutic approach should always be the conservative treatment and our study included only patients that had undergone conservative treatment, but failed to show adequate response. This is however consistent with other recent randomized controlled studies have shown greater improvements in patients after surgery than after conservative treatment [12] [14]. A recent systematic review comparing surgery to conservative treatment in LSS suggested that for patients with radicular pain caused by LSS, in whom a trial of 3 -6 months of conservative treatment had failed, surgery did not improve walking ability but improved pain, function than continuing conservative treatment [10].…”
Section: Discussionsupporting
confidence: 87%
“…A recent systematic review comparing surgery to conservative treatment in LSS suggested that for patients with radicular pain caused by LSS, in whom a trial of 3 -6 months of conservative treatment had failed, surgery did not improve walking ability but improved pain, function than continuing conservative treatment [10]. Small improvements are generally reported by patients treated conservatively and serious complications or deterioration are rare with conservative treatment [1]- [12] [14].…”
Section: Discussionmentioning
confidence: 99%
“…The first therapeutic approach should always be the conservative treatment and our study included only patients that had undergone conservative treatment, but failed to show adequate response. This is however consistent with other recent randomized controlled studies have shown greater improvements in patients after surgery than after conservative treatment [12,14]. A recent systematic review comparing surgery to conservative treatment in LSS suggested that for patients with radicular pain caused by LSS, in whom a trial of 3-6 months of conservative treatment had failed, surgery did not improve walking ability but improved pain, function than continuing conservative treatment [10].…”
Section: Discussionsupporting
confidence: 86%
“…with a small radius of curvature scoliosis and a big radius of curvature installed in adolescence a big radius of curvature, with rapid evolution 5-100 in one year generating both radiculalgia and instability  scoliosis with rotation and rapid evolution to 30-500 affecting several levels  combined stenosis and facet joint cyst  LSS with severe polineuropaty, with or without uni/bilateral paresis The pathophysiology of spinal stenosis causing neurologic symptoms is likely from a combination of anatomic compression of nerve roots as well as impaired blood flow primarily to the nerve roots [1,2,5,6,[10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation